PELAYANAN KELOMPOK KESWADAYAAN MASYARAKAT DALAM KEBERLANJUTAN SANITASI DI DESA BUNGA KECAMATAN PALOLO KABUPATEN SIGI - Parantean, Valentina (Katalogis, 2018)
The study aims to determining the extent of the Service Group Community in the Sustainable of Sanitation in the Bunga Village, inhibiting factors. The method used by researchers is a qualitative research. This study are placed in the Bunga Village Palolo Sub District, Sigi District. While the informant was determined by purposive technique. Data collection techniques in this study using the method observation (observation), interview and documentation. Results were analyzed by using the theory according Taliziduhu services (1997: 63), while the concept of services that are used by the service dimension, is: 1). Right, including start hours until finish services to community; (2). Easy include ease caretaker Community group to provide services and ease caretaker Community group in understanding the problems faced by the community; (3). Fair covers services provided by the management group Community relating to the distribution of clean water to support the sustainability of sanitation; and (4). Fast is the responsiveness on the board of Community in providing the services needed by the community. The results of reseach in the village earn interest at the conclusion that the service group community self-reliance based on the theory of public services according to Taliziduhu Ndraha (1997:63) is only one aspect of speed is accomplished while the three other aspect have not been implemented is: 1). Accuracy because services do not conform with the standarts of operations (swordfish timely and routine daily servicing); 2). Ease because of limited technical skills, knowladge and the number of active groups of community self –reliance, and 3). Juctice as a new clean water is distributed and used by one hundred and seven heads of households out of the the total of two hundred and ninety six heads of households.